Application of electrical tomography to study the internal structure of rock glaciers in Altai - G. Dyakova S.; V. Olenchenko V.; O. Ostanin V.; Г. Дьякова С.; В. Оленченко В.; О. Останин В. (Ice and Snow, 2017)
Internal structure of rock glaciers was investigated at two key sites in Altai by means of electric tomography. It had been found that the rock glaciers of the same type, located at different altitude levels, differ in electric resistances of ice nuclei and the degree of consolidation of the ice material inside of them. Typical characteristics of the ice core of a rock glacier in the high-mountain area are the following: electrical resistivity is about 1000–2000 kOhm∙m and a high degree of the ice consolidation, while the same for the mid-mountain region: the electrical resistivity is 150–300 kOhm∙m and the presence of the talik zones within the glacier body. Using the method of electric tomography for investigation of the internal structure of the rock-glaciers makes possible to reveal presence of frozen soils and ice and to find the upper boundary of occurrence of them from anomalously high specific electric resistance. However, it is not always possible to determine a thickness of the rock-ice formation, and to estimate a degree of its consolidation that does not allow calculating the ice content volume. Limitations of this technology can be overcome by the use of electric tomography in combination with other geophysical methods. На двух ключевых участках территории Алтая выполнено исследование внутреннего строения каменных глетчеров с использованием метода электротомографии. Установлено, что каменные глетчеры, располагающиеся на различных высотных уровнях, отличаются по удельному электрическому сопротивлению и степени консолидации ледяного материала. Для каменно-ледяного ядра каменного глетчера в высокогорье характерны удельное электрическое сопротивление 1000– 2000 кОм∙м и высокая степень консолидации льда, а для каменного глетчера в среднегорье эта величина равна 150–300 кОм∙м, а в теле каменного глетчера присутствуют таликовые зоны.